TSPO-VDAC complex as a regulator of microglial function - Lai, Kei Onn (Nanyang Technological University, 2023)
The translocator protein (TSPO) is a neuroinflammatory biomarker, upregulated in microglia in Alzheimer’s disease (AD) and potentially useful for diagnosis. Despite its potential application as a biomarker, little is known about the molecular functions underlying TSPO function in neuroinflammation. Using transcriptomics and proteomics approaches, I found TSPO deletion to be associated with changes in mitochondrial bioenergetic and phagocytosis pathways in AD-related neuroinflammation. Microglial phagocytosis is an important protective function, clearing amyloid aggregates and preventing AD pathogenesis. In cultured microglia, I found that absence of TSPO impaired phagocytosis, underpinned by reduced actin polymerization, which is energetically demanding and critical for phagocytosis. TSPO directly binds VDAC(Voltage-dependent Anion Channel), which is a metabolic hub binding the glycolytic enzyme, Hexokinase (HK). I hypothesized that TSPO integrates microglia metabolism and phagocytosis through VDAC phosphorylation to regulate mitochondrial HK binding. In TSPO deficient microglia, I found HK enrichment at the mitochondria, while displacement of mitochondrial HK improved the phagocytic efficiencies. Finally, I show that the TSPO-VDAC complex regulates mitochondrial-cytoskeletal dynamics via VDAC interaction with Actin related protein 2(Arp2). Taken together, I propose that TSPO-VDAC complex are involved in regulating the microglial immunometabolic response in phagocytosis.